Experience of using an excimer lamp equipped with UVB dose control system in dermatology - D. V. Schitz; I. E. Torshina; N. V. Nekrasova; T. M. Busko (Biomedical Photonics)
Intermediate ultraviolet (UVB) therapy is considered a relatively safe method of treating skin diseases with an autoimmune component in development compared to medical drug methods, including PUVA therapy. This is due to the small depth of penetration of the rays of this wavelength range into skin, which provides a purely local effect on the human body. Excimer lamps are an alternative to the expensive excimer laser for phototherapy of psoriasis or vitiligo. However, for effective phototherapy using UVB lamps, the distance from an emitter to a patient’s skin must be considered. In this paper, we report on treatment of patients using an excimer lamp, the control unit of which is equipped with an optical system for controlling of ultraviolet radiation dose, which allows automatically calculating the time for a set UVB dose. The article describes the results of phototherapy using an excimer lamp of several cases of psoriasis, vitiligo and other forms of dermatitis with a good therapeutic and cosmetic effect. When using an excimer lamp, not a single case of exacerbation of dermatological diseases was established.